Uji Oligosakarida Ekstrak Tepung Buah Semu Jambu Mete (Anacardium occidentale L.) Terhadap Pertumbuhan Baketri Lactobacillus casei Sebagai Altenatif Prebiotik - Rasydy, La Ode Akbar; Elsa, Restia; Nuraini, Nuraini; Hamidu, La (Jurnal Fitofarmaka Indonesia, 2024)
Cashew pseudo-fruit (Anacardium occidentale L.) is rich in carbohydrates. Carbohydrates can be chemically hydrolyzed into simple monomers such as oligosaccharides. This study aims to ensure the effectiveness of cashew pseudo-fruit flour oligosaccharide extract as an alternative to prebiotics that are able to stimulate the growth of lactic acid bacteria such as Lactobacillus casei. The test was carried out on the growth of Lactobacillus casei bacteria using a 4% concentration cashew pseudo-fruit flour oligosaccharide solution with a dilution of 10-10 using the pour plate method and incubated at a temperature of 37°C for 48 hours to determine the ALT value. The results of the prebiotic parameter test showed the growth of the number of eligible bacterial colonies, namely 25-250 colonies found in dilution 10-4 - 10-8 with an ALT result of 7.3 x 10-6 so it can be concluded that The oligosaccharides extracted from the cashew pseudo-fruit have met the characteristics and criteria as an alternative prebiotic.